2000
DOI: 10.1016/s0735-1097(00)00602-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of thoracic ultrasonography for evaluation of patients with decompensated chronic heart failure

Abstract: Thoracic ultrasonography is a simple, sensitive and accurate method for the evaluation of body fluid accumulation in patients with decompensated CHF. This technique can be used to assist in making the diagnosis of decompensated CHF if other causes of pleural effusion have been clinically ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
2
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 45 publications
3
112
2
3
Order By: Relevance
“…14,20 All four studies included in this review also investigated the accuracy of radiography for detecting pleural effusion. 4,7,12,14 One of these studies found similar results for both methods, and all the other three showed significantly better results for sonography. For radiography, the sensitivity for detecting pleural effusion ranged from 24% to 100% and the specificity ranged from 85% to 100%.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…14,20 All four studies included in this review also investigated the accuracy of radiography for detecting pleural effusion. 4,7,12,14 One of these studies found similar results for both methods, and all the other three showed significantly better results for sonography. For radiography, the sensitivity for detecting pleural effusion ranged from 24% to 100% and the specificity ranged from 85% to 100%.…”
Section: Discussionmentioning
confidence: 74%
“…7 One study performed the index test immediately after performing the reference standard. 4 In another study, 12 the time interval was shorter than two hours in 68% of the cases; shorter than 12 hours in 20% and shorter than 24 hours in 12%. One study 7 did not give such information, and one stated that the maximum time interval was one hour.…”
Section: Quality Of the Studies Includedmentioning
confidence: 88%
See 2 more Smart Citations
“…The explanation for this difference between the two studies remains unclear, but the different approach used for diagnosing clinical deterioration or stability may have contributed. In the present study, the addition of thoracic ultrasonography 9 to standard physical examination may have yielded more accurate identification of patients with decompensated HF based on the objective sign of fluid retention, thus demonstrating the intimate relationship between changes in BNP levels and clinical HF deterioration. In contrast, many patients in the study by Lewin et al 8 were in a state of deterioration based on symptomatic criteria.…”
Section: Relationship Of Body Fluid Status With Levels and Fluctuatiomentioning
confidence: 63%